High pressure/thermal combinations on texture and water holding capacity of chicken batters. (August 2015) - Zheng, Haibo; Xiong, Guoyuan; Han, Minyi; Deng, Shaolin; Xu, Xinglian; Zhou, Guanghong
Abstract: The effects of pressure/thermal combination treatments, i.e. heating before pressure treatment (H-P), pressure treatment before heating (P-H), and heating under pressure (P + H), on chicken batters were investigated using heating (H) as control. The appearance, texture, water holding capacity (WHC), water mobility and distribution, and microstructure were determined. P + H and P-H treatments promoted the batter gelation process, forming a gel with fine strands which resulted in improved appearance, texture and water holding capacity, while H-P treatment, with a similar coarse gel network to H treatment, showed little improvement in texture and appearance, but had increased released water and centrifugation loss. By treating with 200 MPa at 75 °C for 30 min in a single-step process, the chicken sausage had the smoothest appearance, lowest released water and an improved texture. The water mobility and distribution were studied by low-field NMR relaxometry, which showed that H-P and P + H treatment increased the proportion of immobilized water as indicated by T21 relaxation times and population (P21 ). Microstructure further explained the quality improvement of P-H and P + H treatment which could be ascribed to the pressure effects before/during protein denaturation promoting formation of a fine gel network, while H-P treatment limited the resulting effects of pressure on the cooked sample. Hence, P-H and P + H treatment can be used to improve the texture and WHC of gel-type meat products. Industrial relevance: Temperature and pressure are two important thermodynamic parameters which can be combined in several ways in meat product processing. The sequence of pressure and thermal treatment has a significant effect on the quality of meat products. This information will help meat industry to adopt suitable pressure/thermal treatment to produce meat products. Highlights: The sequence of pressure and thermal treatment markedly affect the gel quality. The gel-forming ability was improved by pressurization before or during heating. The texture and WHC properties were further elucidated by microstructure and LF-NMR. Heating under pressure gave the smoothest textural appearance and the highest WHC.